Community Managed Forest Groups and Preferences for REDD+ Contract Attributes: A Choice Experiment Survey of Communities in Nepal (Journal of Forest and Livelihood, 2016)
A significant portion of the world’s forests that are eligible for Reducing Emission from Deforestation and Forest Degradation (REDD+) payments are community managed forests. At the same time, there is a little knowledge in the existing literature about the preferences of households in the communities with community managed forests for REDD+ contracts.We use a choice experiment survey of rural communities in Nepal to understand the respondent’s preferences towards the institutional structure of REDD+ contracts. We split our sample across the communities with community managed forests groups and those without to see how the prior involvement in community managed forest groups’ impact preferences. Results show that respondents care about how the payments are divided between the households and the communities, the restrictions on firewood use, the restrictions on grazing and the level of payments. Finally we use a series of demographic interactions terms to analyze how the institutional arrangements and beliefs about climate change and benefits from the REDD+ program influence respondents’ beliefs. We find that there are no significant differences in the preferences for the REDD+ contract attributes between the Community Forests (CF) and non-CF respondent groups but we find that respondent groups differ in their beliefs about REDD+ payments and the institutional arrangements.Journal of Forest and Livelihood 13(1) May, 2015, Page : 8-19